Carrier Frequency Offset Estimation and I/Q Imbalance Compensation for OFDM Systems. (25th March 2007) - Yan Yan, Feng Feng; Zhu Zhu, Wei-Ping Wei-Ping; Ahmad Ahmad, M. Omair M. Omair
Abstract : Two types of radio-frequency front-end imperfections, that is, carrier frequency offset and the inphase/quadrature (I/Q) imbalance are considered for orthogonal frequency division multiplexing (OFDM) communication systems. A preamble-assisted carrier frequency estimator is proposed along with an I/Q imbalance compensation scheme. The new frequency estimator reveals the relationship between the inphase and the quadrature components of the received preamble and extracts the frequency offset from the phase shift caused by the frequency offset and the cross-talk interference due to the I/Q imbalance. The proposed frequency estimation algorithm is fast, efficient, and robust to I/Q imbalance. An I/Q imbalance estimation/compensation algorithm is also presented by solving a least-square problem formulated using the same preamble as employed for the frequency offset estimation. The computational complexity of the I/Q estimation scheme is further reduced by using part of the short symbols with a little sacrifice in the estimation accuracy. Computer simulation and comparison with some of the existing algorithms are conducted, showing the effectiveness of the proposed method.